Presencia, Frecuencia de los sonidos Sonido Cardiaco S3 y S4 En 13 Caninos En La Ciudad De Bogotá (2023)
In canines, the third and fourth heart sounds S3 and S4 are defined as difficult to auscultate heart sounds and their presence, in most species, can be seen in cases of cardiomyopathies, unlike in equines where they occur consistently. normal way (Ynaraja, s.f.). The S3 and S4 sounds occur during ventricular filling, a moment in which there is blood flow from the atrium to the ventricle, and when it enters the ventricle it generates a shock with the ventricular walls and an end-systolic volume producing the sound ( Silverman, 1990).